Studi Komparatif Kompetensi Siswa Sebelum dan Sesudah Menggunakan LKS IPA Terpadu Bermuatan Literasi Era Digital Kelas VIII SMPN 13 Padang - Arinny Firdausy; Asrizal Asrizal; Amali Putra (PILLAR OF PHYSICS EDUCATION, 2018)
In 2013 curriculum, the science learning was carried out in an integrated form. In the school of science learning conditions hasn’t been successful in implementing the integrated learning. A solution to this problem is the integrated science worksheet by integrating digital age literacy. The aim of this research was to determine the effect of integrated science student worksheet by integrating literacy on competency of grade VIII students. The type of research conducted was a quasi experiment with before-after design. The population in this research were all students of grade VIII SMP Negeri 13 Padang Academic Year 2017/2018. The sample in the research was grade VIII 2 which was obtained by purposive sampling technique. Research instruments for knowledge was written test, observation sheet for attitude aspect and performance assessment sheet forskillsaspects. Data analysis were statistical descriptive analysis and correlated comparision test. The results of this research are the use of integrated student worksheet by integraty digital age literacy gives significant effect on competency of student including, attitude, knowledge, and skill aspects at 95% confidence level. Thus, the use of Integrated science student worksheetby integrity digital age literacy is effective in science approach on grade VIII SMP Negeri 13 Padang.